Taxation of shipping income : a comparative study between Singapore and Malaysia tax treaties. - Chua, Francine Sze Chin. (2008)
This project is a comparative study of the article in Double Taxation Treaties between Singapore and Malaysia that corresponds to Article 8 of the OECD Model Convention. It seeks to shed light on some of the implications arising from taxation of shipping income.